Criminological Aspects: Strategies for Handling Vehicle Registration Certificate Forgery - Sinaga, Maruba Judianto; Lubis, Junaidi; Suriyati, Chairus; Indrayani, Leni; Maria, Juliya (TATOHI: Jurnal Ilmu Hukum, 2026)
Introduction: Vehicle Registration Certificate forgery is a serious crime linked to vehicle theft, not just an administrative violation. From a criminological view, it is driven by the gap between the high demand for cheap transport and strict ownership laws. This inequality creates a black market where stolen vehicles are sold using fraudulent documents to deceive the public. Purposes of the Research: To find out and describe the efforts and strategies implemented by the Kutalimbaru Sector Police in dealing with the crime of forgery of Vehicle Registration Certificate, both through preventive (prevention) and repressive (enforcement) measures. Methods of the Research: This empirical juridical study employs a field research method to analyze the relationship between legal regulations and sociological facts. It evaluates law enforcement effectiveness at the Kutalimbaru Police regarding document falsification. Furthermore, a case approach is utilized by examining specific Vehicle Registration Certificate forgery files handled by the precinct to understand the practical application of criminology in legal proceedings. Findings of the Research: This study offers novelty by examining Kutalimbaru’s unique role as a strategic buffer zone connecting Deli Serdang to surrounding areas. Unlike urban-centric research, it analyzes how this specific geographical location serves as a "safe passage" for distributing fraudulent vehicles and a hideout for stolen property before being integrated into the market using forged Vehicle Registration Certificate documents.